An Examination on Rising Threats of Cyber Security (International Journal of Food and Nutritional Sciences, 2022)
The discipline of securing our computer systems, data, and networks against weaknesses or outside attacks is known as cyber security. The risk of cyberattacks is rising along with the number of internet users. It is crucial that we take the appropriate precautions to defend ourselves against these assaults and prevent unintended harm. The main objective of this study is to concentrate on emerging cyber security trends as new technologies like mobile computing, cloud computing, e-commerce, and social networking become more widely adopted. Although they are crucial, firewalls, antivirus software, and other technical solutions to secure user data and computer networks fall short. The development of information technology as well as Internet activities depends on cyber security. Our attention is typically focused on “Cyber Security” whenever people hear about “Cyber Crimes”. As a result, when we talk about “National Cyber Security”, people first think about how prepared our infrastructure is to handle “Cyber Crimes”. It is essential to teach our folks how to use the cyber infrastructure that our nation is rapidly developing. The results conclude that the goal of cyber security, often referred to as information technology security, is to prevent unauthorized access to, alteration of, or destruction of computers, software, systems, and connections.